Phenotypic variability of Nodilittorina in the paracs reserve - Romero, Leonardo (2002)
Phenotypic characters of Nodilittorinaperuviana y Nodilittorinaaraucana were surveyed in September 1999, on seven rocky shores north of the Paracas Reserve. Shell zigzag white pigmentation and spiral sculpture were recorded for N. peruviana y N. araucana. Significant differences were observed between rocky shores in relation to the above mentioned characteres, which are possibly related to geological and geographical heterogeneity.